Effects of incorporating processed Acacia seed as an emulsifying agent on the quality attributes of beef sausage. (March 2023) - Adiamo, Oladipupo Q.; Netzel, Michael E.; Hoffman, Louwrens C.; Gidley, Michael J.; Osborne, Simone; Sultanbawa, Yasmina
Abstract: In this study, partial or full replacement of 6% soy protein isolate (SPI) with 2, 4 and 6% roasted Acacia seed flour (ASRo) and Acacia seed protein concentrates (ASPC) in emulsified beef sausage were investigated. Emulsion stability and cooking loss were lower in samples formulated with ASPC at all levels and control samples compared to ASRo formulated samples. ASRo generated softer and less chewy sausages than ASPC. Cooked 2% ASPC sausages had similar L* and a* values as the control but with lower colour difference (ΔE) values that were similar to cooked 6% SPI sausages' values. An organized protein network structure was observed in the sausages formulated with ASPC at all levels and in the control samples. Therefore, ASPC, particularly at 2 and 4% inclusion, can be used as a functional ingredient to prepare emulsified beef sausages with good quality attributes.